Determinants of function and dysfunction in irrigation performance, and implications for performance improvement - Perry, C.J. (1995)
This paper suggests definitions of three elements essential to successful irrigation - water rights, infrastructure capable of delivering the service implied in the water right, and assigned operational responsibilities. Depending on whether the basic elements are promptly matched, systems are defined as 'functional' or 'dysfunctional.' The importance of interactions among these factors is illustrated through field examples. It is argued that performance analysis of dysfunctional systems is problematic, and functionality may be a prerequisite to significant improvements in performance. The definition of water rights, particularly as undocumented and unregulated usage develops, is likely to present the most difficult challenge to achieving functionality.